Puerulus and early juvenile recruitment of the rock lobster jasus lalandii in relation to the environment at Lüderitz Bay, Namibia - Keulder, Felicia Juanita (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2005)
A global decline in the lobster fishery has necessitated the growout of wild-caught postlarvae (pueruli) on farms to meet the worlds lobster demand. A limited knowledge on puerulus settlement in the West Coast rock lobster (Jasus lalandii) constitutes a major barrier for J. lalandii culture development in Southern Africa. As an extension of an existing long-term puerulus monitoring program of the Ministry of Fisheries and Marine Resources of Namibia, the present study monitored puerulus recruitment (supply), puerulus condition and juvenile growth of J. lalandii and their relationship with environmental variables on an oyster farm at Lüderitz Bay, Namibia. Implications for lobster aquaculture and fisheries management are discussed. Oyster bags, crates and collectors were sampled daily, weekly and bimonthly, for pueruli and juveniles, respectively, between August 2001 and July 2003 to establish spatialtemporal patterns in their distribution. Animals were transported to the laboratory for morphometric analyses where they were staged as puerulus (Pt = transparent; Pp = pigmented) and juvenile lobsters. The carapace lengths (0.1mm CL) and wet weights (0.01gram) of animals were recorded. Carapace length frequencies were subjected to Modal Progression analysis to identify early juvenile cohorts and calculate their growths. The weight-length ratios calculated and percentage fat content were used as indices of nutritional condition. Seasonal peaks in puerulus and juvenile abundance were estimated using Periodic Regression analysis. The relationships of puerulus and juvenile abundance with respect to sea surface temperature (SST), wind speed-direction, moon phase, swell and tidal range were established using time lag analysis (ADL). Transparent pueruli were randomly distributed on oyster bags and crates, and also between collector sites, suggesting that they have no particular settlement preference for certain areas on these structures (p>0.05; n=150). Pigmented puerulus (p<0.05; n=566) and juveniles (p<0.05; n=3528) preferred structurally complex structures that provided better shelter such as crates, which were more sheltered from sea swells, compared to oyster bags. Among oyster rafts, pigmented puerulus and juveniles preferred occupying the sheltered and centred raft areas, which provided better protection from wave action, compared to exposed raft areas, which were exposed to the incoming swell. Puerulus and juvenile lobster appeared to recolonise adjacent bags and crates, and possibly migrate to the substrate and off the farm due to the disturbance of the habitat during harvesting. The booth crevice collector was more efficient in collecting puerulus possibly due to the high structurally complex habitat and the better shelter they provided compared to the hogshair collector. The occupation of structurally complex habitats by early benthic stages may be related to morphological changes associated with metamorphosis. Puerulus settlement peaked during early spring (August-September) and was related to low sea surface temperatures (12.3Â°C), strong south winds, and moderate swells in the week preceding settlement. These conditions are synonymous with the "spring upwelling" season of the Lüderitz upwelling cell in the central Benguela current region. Puerulus nutritional condition peaked during this period possibly due to high levels of planktonic food (due to high nutrients from upwelling) that was available to the late stage phyllosoma larvae further offshore. A "good" puerulus settlement year during 2000 was associated with lower than average SST (11.6Â°C) and strong south winds and was followed by "poor" puerulus settlement years during 2001 and 2002 when higher than average SST were experienced with below average wind speeds experienced during 2001 only. Puerulus of J. lalandii recruited in high numbers into Lüderitz Bay during the new moon, full moon and last quarter moon phases by making use of the increased tides during these phases of the lunar cycle. Peak juvenile abundance during early summer (November-December) lagged by 8 weeks was significantly correlated with peak puerulus abundance. Puerulus size was similar (8.5"“9.7mm CL) over the study period. Juvenile cohorts, 9.9-20.6mm CL in size recruited in 2 distinct waves in August 2001-June 2002 and July 2002-February 2003. The 2001/2002 recruits had higher monthly growth increments and better nutritional condition compared to 2002/2003 recruits. Peak frequencies of 2nd moult juveniles (9.9- 10.8mm CL) occurred in September of both recruitment events with nutritional condition being poorest during the 2002/2003 event. The nutritional condition of the settling puerulus did not appear to be related to the subsequent growth of juvenile lobster. These preliminary results suggest that pueruli recruit once a year mainly during late winter/ early spring under conditions typical of coastal upwelling in the Benguela current near Lüderitz. It appears that puerulus settlement is driven by favourable shoreward currents, which help in transporting puerulus to their settlement grounds. Puerulus supply is highly variable between years, which appears to be consistent with a highly variable Benguela environment. The oyster farm supported a substantial standing stock averaging 123 800 lobster per day (range: 22 600-325 300 lobster per day) of which 26 600 were puerulus and 97 200 were juveniles, that may have been harvested once off on any given day during the sample period. Monthly harvesting of the total lobster standing stock during the one and a half year sampling period was just over 2 million lobsters (505 700 pueruli and 1.85 million juveniles) and would potentially have been sufficient seed for a 200 ton lobster production in puerulus lobster growout facilities. In the light of high inter-annual variation in puerulus settlement observed at Lüderitz, the seed supply at the Lüderitz oyster farm is clearly limited and therefore it is prudent that other sites of high puerulus settlement is established before large commercial scale lobster growout can commence. The migration of lobster off the farm suggested that these lobsters potentially recruit to the fishery and therefore harvesting the entire standing stock on the farm may have adverse negative effects on the wild fishery. A policy decision will be required as to whether more efficient harvesting of lobster from the farm should be allowed. If puerulus removal in J. lalandii for aquaculture is allowed in the near future, it should be conducted on an experimental scale or small commercial scale until the potential effects on recruitment into the fishery are clearer.
Keywords: Jasus lalandii; Lobster fisheries -- Namibia; Lobster culture -- Namibia